Development of quantitative imaging mass spectrometry (q‐IMS) for drug visualization using animal tissues. (2nd September 2018) - Takeo, Emi; Shimma, Shuichi
Abstract : Quantitative imaging mass spectrometry ( q ‐IMS) is a frontier topic of research in drug analysis. Although many q ‐IMS methodologies have been reported, validation of the method is insufficient. We have investigated the feasibility of coupling q ‐IMS with liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) to develop a verifiable method. The approach combines quantitative LC‐MS/MS information with the spatial distribution information obtained by IMS. This paper compares measured drug quantities with those estimated using IMS. The target drug, erlotinib, is a tyrosine kinase inhibitor of non‐small‐cell lung cancer. The quantitative accuracy of our q ‐IMS method in an animal model study is approximately 17%. Measurements were conducted on mouse liver and brain tissues before and after erlotinib administration. Erlotinib is delivered to the brain, although the concentration is 10 4 times smaller than that found in the liver.